ANALISIS PERHITUNGAN PEGADAIAN UMUM DAN PEGADAIAN SYARIAH DALAM KONTEKS GADAI EMAS - Ridwan Tabe (IAIN Manado, 2017)
AbstractThis paper discusses about the calculation analysis of general and sharia pawnshop in the context of gold pawn, with the aim of giving an understanding about the differences of the calculation in both. Both pawnshops bring the concept that the pawn is a system of lending and borrowing between the parties having lack of fund to those having abundant of fund by pledging valuables thing to convince the lender. The study shows that general and sharia pawnshops are equally using Metal Estimated Standard, and have four different components of the calculation: an estimate, money lending, administrative cost, and interest expense, but the distinction in the sharia pawnshop is the interest to be replaced by surrogate (ijaroh) The difference between the interest with ijaroh -if it is seen based on a scale of days- the general pawnshop is generally more affordable because the provisions of interest expense in it, is generally calculated based on the cycles per 15 days and interest calculation is done twice a month, whereas in sharia pawnshops, the ijaroh calculation is done three times a month or calculated / 10 days. But if it is seen from the profit scale of the total amount between interest and ijaroh, the sharia pawnshop is cheaper than the general pawnshop. It is seen from thecalculation result in the same case by using of a period of 120 days, so the general pawnshop shows the value of installment inRp. 450 800, while the sharia pawnshop shows the value of installment inRp. 450,000, -.Key words: Calculation, general pawnshop, sharia pawnshop. um, gadai syariah